A radiation-proof and anti-vertigo diffusion film and a preparation method thereof

The amidoxime structure is introduced by reacting hydroxylamine and polyacrylonitrile and complexing with rare earth elements to prepare a modified diffusion film blended with polyacrylonitrile and polycarbonate, which solves the problem of the light transmittance of existing materials after adding modifiers, and achieves an effective combination of radiation and anti-vertigo functions.

CN119144138BActive Publication Date: 2025-03-21湖南壹鑫科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411376792.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-03-21
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

After adding modifiers, existing radiation-proof and anti-vertigo materials have reduced light transmittance and are difficult to achieve a balance between light transmittance and haze, and cannot effectively combine radiation-proof and anti-vertigo functions.

Method used

The amidoxime structure is introduced by reacting hydroxylamine with polyacrylonitrile, and the rare earth elements are complexed to prepare modified polyacrylonitrile, and then physically blended with polycarbonate to prepare a diffusion film that has both radiation and anti-vertigo functions.

Benefits of technology

It realizes a significant increase in haze while maintaining a high light transmittance, enhances the radiation resistance of the material, and reduces the preparation cost and complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144138B_ABST
    Figure CN119144138B_ABST
Patent Text Reader

Abstract

The invention discloses a radiation-proof and anti-vertigo diffusion film and a preparation method thereof, and belongs to the field of materials science. The diffusion film comprises 92-98 parts of polycarbonate, 2-7 parts of modified polyacrylonitrile, and 0.3-1 parts of antioxidant by weight, and uses hydroxylamine to react with polyacrylonitrile to introduce amidoxime structure, and utilizes its ion complexing ability to complex rare earth ions, and then granulates after hot-melt extrusion with polycarbonate, and then prepares a diffusion film of a certain thickness, and the prepared diffusion film has a light transmittance of up to 78%, a haze of up to 78.1, and a radiation-proof M value of up to 0.143279. The diffusion film has the characteristics of novel structure, simple preparation, and good radiation-proof and anti-vertigo effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a radiation-proof and anti-vertigo diffusion film and a preparation method thereof. Background Art

[0002] With the advent of the intelligent information age, smart phones, smart TVs, high-efficiency lighting devices and solar cells have entered thousands of households and gradually become an indispensable part of everyone's daily life. These devices all require the use of light extraction units, which all contain a light diffusion material made of polymer composite materials to improve the diffusion and extraction effect of light. Point light sources with too high luminous intensity are prone to glare. The use of light diffusion materials can effectively improve this problem. While maintaining the luminous intensity, the dazzling point and line light sources are diffused into soft surface light sources. This material can diffuse the incident light that was originally a point light source and a line light source into a line light source and a surface light source through scattering and refraction, greatly increasing the diffusion area of ​​light and reducing the glare caused by light concentration.

[0003] Light diffusion materials can be basically divided into four categories according to different preparation methods: surface microstructure type, volume diffusion type, composite type and new light diffusion materials. Surface microstructure materials use photolithography and imprinting to construct microstructures such as microlenses, three-dimensional porous structures or rough concave and convex surfaces on the surface of the material, and transmit, reflect and scatter the incident light to achieve light diffusion performance. This preparation method generally requires expensive precision instruments and has low production efficiency, which makes it difficult to meet market demand. The volume diffusion type is generally composed of matrix materials and light diffusion particles, which is the current mainstream solution. Composite light diffusion materials have surface microstructures, basic materials and light diffusion particles at the same time, which obviously increases the cost.

[0004] With the continuous development of national defense technology, radioactive medicine, and nuclear technology applications, as well as the increasing prominence of environmental problems, various radioactive rays are widely used, and the harm of radiation to the human body and the damage to the environment are gradually recognized by humans. People have an increasing demand for products with radiation protection functions. There are three ways to prepare radiation protection materials: physical blending, chemical blending, and a combination of the two. Physical blending is to add inorganic or organic chemicals to the basic materials without chemical reactions to achieve radiation protection. Chemical blending adds modifiers or modified materials to the basic materials to form composite materials to achieve radiation protection. At present, rare earth radiation shielding materials are an emerging research direction for radiation protection materials, and there are many domestic studies. The small size effect, surface and interface effect, and quantum size effect of nanomaterials have a good promoting effect on improving the physical properties and shielding effect of materials. They have been used in the preparation of shielding materials and have achieved good results.

[0005] From the above discussion, it can be seen that in the preparation of radiation protection and anti-vertigo materials, the methods of material modification are basically the same, and can be attributed to physical or chemical or a combination of the two methods. If an anti-vertigo and an anti-radiation modifier are added to the basic material, it is possible to obtain a functional material with two functions by balancing the transmittance and haze. However, the actual situation is often unsatisfactory. This is because with the superposition of the types of modifiers, the transmittance will inevitably decrease, and it will also be more difficult to achieve a balance between transmittance and haze. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a radiation-proof and anti-vertigo diffusion film. Another purpose of the present invention is to provide a method for preparing the radiation-proof and anti-vertigo diffusion film.

[0007] Technical solution: A radiation-proof and anti-vertigo diffusion film, comprising the following components: polycarbonate, modified polyacrylonitrile, and an antioxidant, wherein the modified polyacrylonitrile has a structure as shown in Formula 1:

[0008]

[0009] Here, M is one of La, Ce, Pr, and Nd.

[0010] Preferably, the diffusion membrane comprises 92-98 parts by weight of polycarbonate, 2-7 parts by weight of modified polyacrylonitrile, and 0.3-1 parts by weight of antioxidant.

[0011] Preferably, the molecular weight of the modified polyacrylonitrile is 2.5×10 4 ~5×10 4 .

[0012] A method for preparing an anti-radiation and anti-vertigo diffusion film comprises the following steps:

[0013] S1. Dissolve polyacrylonitrile in a mixed solvent of N,N-dimethylformamide and methanol, then add 50% hydroxylamine aqueous solution, heat to 50-100°C for reaction, add purified water after the reaction, keep warm and stir for 2h, precipitate solid, cool to 10-30°C and continue stirring for 2h, filter, wash the solid twice with water, and obtain modified polyacrylonitrile of formula 2;

[0014]

[0015] S2, dissolving the metal oxide in a 3N hydrochloric acid solution, then adjusting the system pH to 5-6, adding the compound of formula 2 prepared in step S1 and N,N-dimethylformamide, stirring at room temperature for 10 hours, adding deionized water, filtering, washing the filter cake with water twice, and vacuum drying to obtain modified polyacrylonitrile of formula 1;

[0016]

[0017] S3, weighing 92-98 parts of polycarbonate, 2-7 parts of modified polyacrylonitrile of formula 1, and 0.3-1 parts of antioxidant by weight, adding them into a twin-screw extruder, blending at 240-295° C. and a screw speed of 100-120 r / min, and after extrusion, drawing and pelletizing;

[0018] S4, adding the pelletized material of step S3 into an injection molding machine, with the injection molding temperature at 300° C., to form a diffusion film with a thickness of 0.1 mm to 5 mm.

[0019] Preferably, in step S1, the mass ratio of polyacrylonitrile to the hydroxylamine aqueous solution is 1:2-10.

[0020] Preferably, in step S2, the metal oxide is one or a combination of lanthanum oxide, cerium oxide, praseodymium oxide and neodymium oxide.

[0021] Preferably, in step S2, the pH of the system is adjusted to 5-6 with sodium hydroxide solution.

[0022] Preferably, in step S4, the injection pressure and speed are 90-150 MPa and 50%-98% respectively.

[0023] Beneficial effects: The present invention introduces an amidoxime structure by reacting hydroxylamine with polyacrylonitrile, and then utilizes the complexing ability of the amidoxime structure for ions to further complex rare earth elements with radiation protection to prepare modified polyacrylonitrile, which is then physically blended with PC to prepare a membrane material with both radiation protection and anti-vertigo properties. The method is novel, and the modifier is cheap and easily available, the preparation method is simple, and the chemical reaction and product separation are easy to operate, which has huge market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a particle shape analysis diagram of the modified polyacrylonitrile with structure of formula 1 prepared in Example 1.

[0025] Figure 2 This is a graph showing the particle size analysis results of the modified polyacrylonitrile of formula 1 prepared in Example 1.

[0026] Figure 3 This is the thermal analysis spectrum of the diffusion film prepared in Example 2. DETAILED DESCRIPTION

[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.

[0028] Example 1

[0029] Weigh the molecular weight 2.5×10 4 ~3.5×10 485g of polyacrylonitrile, 45g of N,N-dimethylformamide, 850g of methanol, and then 255g of 50% hydroxylamine solution, heated to 90°C for reaction, reacted for 15h, added 600ml of purified water, stirred at this temperature for 2h, after solid precipitated, cooled to 20°C and stirred for 2h, filtered, and the filter cake was washed twice with 400ml of water to obtain a compound of formula 2;

[0030] Weigh 2.0 g of lanthanum oxide, add it to 50 ml of 3N hydrochloric acid solution, stir and react for 1 h, adjust the system pH to 5-6 with 10% sodium hydroxide solution, add the compound of formula 2 prepared above, 40 g of N,N-dimethylformamide, stir and react at room temperature for 10 h, add 200 ml of deionized water, stir for 30 min, filter, wash the filter cake with water twice, and vacuum dry to obtain modified polyacrylonitrile with the structure of formula 1;

[0031] The above-mentioned dry solid particle shape was analyzed using a ZML310 particle size analyzer. Figure 1 As shown;

[0032] The particle size analysis was performed using a Bettersize 2600 laser particle size analyzer with dry sampling. The results are shown in the attached figure. Figure 2 As shown;

[0033] Weigh 92 parts of polycarbonate, 7 parts of modified polyacrylonitrile of formula 1, and 0.5 parts of antioxidant by weight, add them into a twin-screw extruder, set the temperature at 240°C-245°C-290°C-290°C-290°C-290°C-295°C-295°C-295°C-295°C, blend at a screw speed of 100r / min, and after extrusion, draw strands and pelletize;

[0034] The above-mentioned pelletized material was added into an injection molding machine, and the injection molding temperature was 300° C., and the injection molding pressure and speed were 150 MPa and 80% respectively, to produce a diffusion membrane 1 with a thickness of 1.0 mm.

[0035] Example 2

[0036] Weigh 94 parts of polycarbonate, 5 parts of modified polyacrylonitrile of formula 1, and 0.5 parts of antioxidant by weight, add them into a twin-screw extruder, set the temperature at 240°C-245°C-290°C-290°C-290°C-290°C-295°C-295°C-295°C-295°C, blend at a screw speed of 100r / min, and after extrusion, draw strands and pelletize;

[0037] The above-mentioned pelletized material was added into an injection molding machine, and the injection molding temperature was 300° C., and the injection molding pressure and speed were 150 MPa and 80% respectively, to produce a diffusion membrane 2 with a thickness of 1.0 mm.

[0038] Thermal analysis: Thermogravimetric / differential thermal analysis instrument, Shimadzu, Japan

[0039] Heating rate: 20℃ / min Temperature range: rt-400℃ as attached Figure 3 Shown

[0040] Example 3

[0041] Weigh 96 parts of polycarbonate, 3 parts of modified polyacrylonitrile of formula 1, and 0.5 parts of antioxidant by weight, add them into a twin-screw extruder, set the temperature at 240°C-245°C-290°C-290°C-290°C-290°C-295°C-295°C-295°C-295°C, blend at a screw speed of 100r / min, and after extrusion, draw strands and pelletize;

[0042] The above-mentioned pelletized material was added into an injection molding machine, and the injection molding temperature was 300° C., and the injection molding pressure and speed were 150 MPa and 80% respectively, to produce a diffusion membrane 3 with a thickness of 1.0 mm.

[0043] Comparative Example 1

[0044] 94 parts of polycarbonate, 5 parts of polyacrylonitrile and 0.5 parts of antioxidant were weighed by weight, added into a twin-screw extruder, and the temperature was set at 240°C-245°C-290°C-290°C-290°C-290°C-295°C-295°C-295°C-295°C, and the screw speed was 100r / min for blending. After extrusion, the mixture was stranded and pelletized;

[0045] The above pelletized material was added into an injection molding machine, the injection temperature was 300° C., the injection pressure and speed were 150 MPa and 80% respectively, and a comparative film 1 with a thickness of 1.0 mm was prepared.

[0046] Comparative Example 2

[0047] Weigh the molecular weight 2.5×10 4 ~3.5×10 4 85g of polyacrylonitrile, 45g of N,N-dimethylformamide, 850g of methanol, and then 255g of 50% hydroxylamine solution, heated to 90°C for reaction, reacted for 15h, added 600ml of purified water, stirred at this temperature for 2h, after solid precipitated, cooled to 20°C and stirred for 2h, filtered, the filter cake was washed twice with 400ml of water, and vacuum dried to obtain the compound of formula 2;

[0048] Weigh 94 parts of polycarbonate, 5 parts of modified polyacrylonitrile of formula 2, and 0.5 parts of antioxidant by weight, add into a twin-screw extruder, set the temperature at 240°C-245°C-290°C-290°C-290°C-290°C-295°C-295°C-295°C-295°C, blend at a screw speed of 100r / min, and after extrusion, draw into strands and pelletize;

[0049] The above pelletized material was added into an injection molding machine, the injection temperature was 300° C., the injection pressure and speed were 150 MPa and 80% respectively, and a comparative film 2 with a thickness of 1.0 mm was prepared.

[0050] Transmittance and haze test:

[0051] Instrument: Color Haze Meter (CS-720)

[0052] Light source: Class A

[0053] Measurement standard: ISO 14782

[0054] Table 1 Light transmittance of diffusion films of embodiments and comparative examples

[0055]

[0056] The above results show that the light transmittance decreases slightly with the addition of modified polyacrylonitrile, and within the range of 3-7 parts of added amount, the light transmittance is not related to the added amount.

[0057] Table 2 Haze of diffusion membranes of examples and comparative examples

[0058] sample Polycarbonate Modified polyacrylonitrile Haze Example 1 - Diffuser membrane 1 92 copies 7 servings 78.1 Example 2 - Diffuser membrane 2 94 copies 5 servings 69.9 Example 3 - Diffusion membrane 3 96 copies 3 servings 60.8 Comparative Example 1-Comparative Film 1 94 copies 5 parts (polyacrylonitrile) 15.7

[0059] The above results show that the addition of modified polyacrylonitrile makes the haze value much higher than that of the control group of comparative film 1. In the range of 3-7 parts of addition, the haze increases with the increase of addition amount, and the maximum increase is 3.97 times.

[0060] Radiation protection performance test:

[0061] Instruments: high stability X-ray machine (Philips, Germany), precision integrating galvanometer (Austrian Scientific Research Center);

[0062] Sample preparation: Take the films prepared in the examples and comparative examples and make samples with a size of 12 mm × 14 mm × 1.0 mm;

[0063] Test method: Take a dot with a radius of 2.5 cm on the sheet each time and take the average value of 5 points;

[0064] Table 3 Radiation protection performance data of materials in embodiments and comparative examples - tube voltage 60KVp

[0065]

[0066] The above results show that as the proportion of modified polyacrylonitrile increases, its lead equivalent value per unit thickness increases, indicating that the radiation protection ability is enhanced, while Comparative Example 1 is used as a blank, and Comparative Example 2 adds modified polyacrylonitrile but does not form a complex with the rare earth element, and has basically no radiation protection effect.

[0067] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in the field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A radiation-proof and anti-vertigo diffusion film, characterized in that: The invention comprises the following components by weight: 92-98 parts of polycarbonate, 2-7 parts of modified polyacrylonitrile, and 0.3-1 parts of antioxidant, wherein the structure of the modified polyacrylonitrile is as shown in Formula 1: Here, M is one of La, Ce, Pr, and Nd.

2. The radiation-proof and anti-vertigo diffusion film according to claim 1, characterized in that: The molecular weight of modified polyacrylonitrile is 2.5×10 4 ~5×10 4 .

3. A method for preparing the radiation-proof and anti-vertigo diffusion film according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Dissolve polyacrylonitrile in a mixed solvent of N,N-dimethylformamide and methanol, then add 50% hydroxylamine aqueous solution, heat to 50-100°C for reaction, add purified water after the reaction, keep warm and stir for 2h, precipitate solid, cool to 10-30°C and continue stirring for 2h, filter, wash the solid twice with water, and obtain modified polyacrylonitrile of formula 2; S2, dissolving the metal oxide in a 3N hydrochloric acid solution, then adjusting the system pH to 5-6, adding the compound of formula 2 prepared in step S1 and N,N-dimethylformamide, stirring at room temperature for 10 hours, adding deionized water, filtering, washing the filter cake with water twice, and vacuum drying to obtain modified polyacrylonitrile of formula 1; S3, weighing 92-98 parts of polycarbonate, 2-7 parts of modified polyacrylonitrile of formula 1, and 0.3-1 parts of antioxidant by weight, adding them into a twin-screw extruder, blending at 240-295° C. and a screw speed of 100-120 r / min, and after extrusion, drawing and pelletizing; S4, adding the pelletized material of step S3 into an injection molding machine, with the injection molding temperature at 300° C., to form a diffusion film with a thickness of 0.1 mm to 5 mm.

4. The method for preparing the radiation-proof and anti-vertigo diffusion film according to claim 3, characterized in that: In the step S1, the mass ratio of polyacrylonitrile to the hydroxylamine aqueous solution is 1:2-10.

5. The method for preparing the radiation-proof and anti-vertigo diffusion film according to claim 3, characterized in that: In step S2, the metal oxide is one or a combination of lanthanum oxide, cerium oxide, praseodymium oxide, and neodymium oxide.

6. The method for preparing the radiation-proof and anti-vertigo diffusion film according to claim 3, characterized in that: In step S2, the pH of the system is adjusted to 5-6 with sodium hydroxide solution.

7. The method for preparing the radiation-proof and anti-vertigo diffusion film according to claim 3, characterized in that: In step S4, the injection pressure and speed are 90-150 MPa and 50%-98% respectively.

Citation Information

Patent Citations

  • Optical high-transparency polycarbonate material and preparation method thereof

    CN102382441A

  • Ultraviolet response type rare earth light conversion film and application thereof

    CN103745981A

  • Self-supporting M-N / C oxygen reduction catalyst and preparation method and application thereof

    CN113206260A

  • Infrared reflective dark colored polycarbonate composition

    US20160229991A1